Identifying RNA 5-methylcytosine sites via pseudo nucleotide compositions. Issue 11 (17th August 2016) - Feng, Pengmian; Ding, Hui; Chen, Wei; Lin, Hao
Abstract : RNA 5-methylcytosine (m 5 C) has been discovered from archaea to eukaryotes, which is catalyzed by RNA methyltransferase. Abstract : RNA 5-methylcytosine (m 5 C) plays an important role in numerous biological processes. Accurate identification of the m 5 C site is helpful for a better understanding of its biological functions. However, the drawbacks of the experimental methods available preclude progress towards the identification of the m 5 C site. As an excellent complement to experimental techniques, computational methods will facilitate the identification of m 5 C. In the present study, a support vector machine based-method is proposed to identify m 5 C sites in Homo sapiens . In this method, RNA sequences are encoded using the pseudo dinucleotide composition in which three RNA physiochemical properties are incorporated. It was observed by the jackknife cross-validation that the overall success rate achieved by the proposed model is 90.42%. This result indicates that the proposed model holds the potential to become a useful tool for the identification of m 5 C sites.